Metastatic disease and major adverse cardiovascular events preceding diagnosis are the main determinants of disease-specific survival of pheochromocytoma/paraganglioma: long-term follow-up of 303 patients - Raber, Wolfgang; Schendl, Raphael; Arikan, Melisa; Scheuba, Andreas; Mazal, Peter; Stadlmann, Valerie; Lehner, Reinhard; Zeitlhofer, Petra; Baumgartner-Parzer, Sabina; Gabler, Cornelia; Esterbauer, Harald (Frontiers in Endocrinology, 2024)
Purpose The natural history in unselected cohorts of patients with pheochromocytoma/ paraganglioma (PPGL) followed for a period >10 years remains limited. We aimed to describe baseline characteristics and outcome of a large cohort and to identify predictors of shorter survival. Methods This retrospective single-center study included 303 patients with newly diagnosed PPGL from 1968 to December 31, 2023, in 199 prospectively supplemented since July 2020. Mean follow-up was 11.4 (range 0.3-50) years, germline genetic analyses were available in 92.1%. The main outcome measures were overall (OAS), disease-specific (DSS), recurrence-free (RFS) survival and predictors of shorter survival evaluated in patients with metastases at first diagnosis (n=12), metastatic (n=24) and nonmetastatic (n=33) recurrences and without evidence of PPGL after first surgery (n=234). Results Age at study begin was 49.4 ± 16.3 years. There were 72 (23.8%) deaths, 15 (5.0%), 29 (9.6%) and 28 (9.2%) due to PPGL, cardiovascular disease (CVD) and malignant or other diseases, respectively. Median OAS, DSS1 (tumor-related) and DSS2 (DSS1 and death caused by CVD) were 4.8, 5.9 and 5.2 years (patients with metastases at first diagnosis), 21.2, 21.2 and 19.9 years, and 38.0, undefined and 38.0 years (patients with metastatic and with nonmetastatic recurrences, respectively). Major adverse cardiovascular events (MACE) preceded the first diagnosis in 15% (n=44). Shorter DSS2 correlated with older age (P ≤ 0.001), male sex (P ≤ 0.02), MACE (P ≤ 0.01) and primary metastases (P<0.0001, also for DSS1). Conclusion The clinical course of unselected patients with PPGL is rather benign. Survival rates remain high for decades, unless there are MACE before diagnosis or metastatic disease.